Variations in soil phosphorus levels in Acacia hybrid plantations across different ages in southern Vietnam - Karam Singh, Daljit Singh; Chau, M.H.; Cuong, L.V; Hung, B.M; Quy, N.V. (Malaysian Society of Soil Science, 2024)
Phosphorus (P) plays a crucial role in shaping nutrient cycles within terrestrial ecosystems. Understanding the fluctuations and factors influencing soil P in Acacia hybrid plantations in southern Vietnam is essential. The scarcity of comprehensive studies focusing on this specific ecosystem underscores the urgent need for further research to bridge this knowledge gap. This study aims to assess alterations in soil total phosphorus (TP) and available phosphorus (AP) levels and storage, as well as to identify the factors influencing soil TP and AP concentrations based on soil and forest stand characteristics across five different ages (2, 4, 6, 8, and 10 years old) of Acacia hybrid plantations within the Langa Forestry Company in southern Vietnam. Soil samples were collected at five different depths (0–20, 20–40, 40–60, 60–80, and 80–100 cm). The results revealed that soil TP and AP concentrations in the five stands increased with stand age, showing a significant decrease with soil depth. Soil TP and AP stocks increased from 4.78-5.35 Mg ha−1 and from 0.12-0.50 Mg ha−1 , respectively, as the stand developed. Additionally, soil TP and AP stocks displayed noticeable aggregation in the topsoil, with over 40% of TP storage and over 50% of AP storage occurring within 0-40 cm depth. The structural equation model (SEM) suggested that both soil parameters (i.e., soil bulk density and pH) and forest stand characteristics (i.e., plant biomass) significantly influenced soil TP and AP concentrations. Mainly, soil properties parameters had a more substantial impact on soil P concentrations than forest stand features parameters. Our findings offer new insights into soil phosphorus dynamics, with significant implications for Acacia hybrid forests' protection and sustainable management.